(3JGQjN eNJUQ ef Chd BOe Edi GdefUhQ Hf CHj YGeQs - (3CHhGdMSf Ydj Hf Gdabjg CHj YHO Gddg Hf CHj GdSQhQ Hf YHO GdQMef Hf YHO GdYRjR GdQhMjs
(3ChdgG (B:s
(3aEfj PGcQ aj cJGHj gPG Gdbhd aj G dReGf s
(3fSNI ocJHJ dNRGfI Gdedc GdfGUQ aQL Hf GdXGgQ HQbhb SfI (B910 (3eLehY ajg ef GdJGQjN ef Chd BOe Ydjg GdSdGe Edi BNQ OhdI Gdedc GdfGUQ aQL Hf HQbhb QMeg Gddgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B66 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs